The Effects of CaO-TiO2 Calcination Temperatures on the Catalyst Characterization and Palm Biodiesel Psychochemical Properties - Syed Abdul Mutalib, Sharifah Nurul Balqis; Nurul Fitriah Nasir (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Biodiesel is the new innovative substitute for petroleum and there are many vegetable oils could be used as the feedstock and one of it is vegetable palm oil (VPO). This research is conducted to analyze CaO-TiO2 catalysts under calcination process of temperature 200℃, 400℃, 600℃ and 800℃ then produce and test biodiesel oil. The catalysts then go through analysis using X-Ray diffraction analysis (XRD) analysis, Scanning electron microscopy (SEM) analysis and Fourier Transform Infrared Spectroscopy (FTIR) analysis. Through transesterification biodiesel is extracted with reaction time of 120 minutes and reaction temperature of 65℃ and 10%wt of CaO-TiO2 catalyst of 9:1 molar ratio of methanol and VPO. The biodiesel then will be tested for psychochemical properties that is the density and kinematic viscosity of the biodiesel. This analysis will be based on previous studies and also ASTM D6751 standards for biodiesel properties. The catalysts showed all the particles from different elements distributed accurately throughout the SEM test. Based on the result of density and kinematic viscosity it is proven that the biodiesel created from catalyst CaO-TiO2 under calcination process of 800℃, shows accurate results accordance to ASTM D6751 standards.